Atlas of surgical techniques in trauma - Demetriades, Demetrios; Inaba, Kenji; Velmahos, George (Cambridge : Cambridge University Press, 2015)
Using high-quality intra-operative photos of fresh, ventilated and perfused human cadavers, this atlas of surgical techniques creates a unique new resource for trauma surgeons. The critical aspects of each surgical exposure and procedure are clearly demonstrated step-by-step in these realistic models, allowing the reader rapidly to understand technical key points which can be complex to describe. With more than 600 illustrations, it provides a highly visual summary of the critical anatomy, procedural sequencing, and pitfalls associated with trauma procedures. Informed by the editors' decades of collective experience in the field of trauma, in some of the busiest trauma centers in the world, the book is an invaluable quick reference for both common and uncommonly performed procedures. As such, it is ideal for trainee trauma surgeons, as well as those in civilian or military practice. Also of interest to trauma fellows and emergency medicine physicians.
Title from publisher's bibliographic system (viewed on 13 May 2016).